Enhancing crop productivity through soil and nutrient management - Kumar, Praveen; Panwar, N. R.; Kasana, R. C.; Saritha, M.; Burman, Uday (Indian Farming, 2018)
The area under crops and cropping intensity are increasing day-by-day to feed ever growing man and animal population in arid zone. This trend can be continued for a long-time only by ensuring that plants had an adequate and balanced supply of nutrients and appropriate environments exist in soil for nutrients to be available to crop plants. Nutrient levels in arid soils are constrained by extremes of environments and can not meet the production requirements of today. External addition of nutrients in arid conditions pose economic burden and also carry risk. Two major approaches were discussed to achieve higher production levels with lower economic risks. First is the application of external inputs especially nitrogen (N) in optimum quantity with site specific management, and second is enhancing internal nutrients circulation by using crop residues and manure, cereal legume rotation, intercropping of legumes in cereals and mycorrhiza.